Code-Switching Used by Multilingual Person (Jerome Polin) in Nihonggo Mantappu Youtube Video - Indah Pareza; Nur Rosita (Universitas Negeri Padang, 2023)
Language contact is the phenomenon of using two or more languages at the same time and place. The purpose of using two or more languages in communication is to build good communication based on social factors. Language contact caused various linguistic phenomena, such as bilingualism, multilingualism, diglossia, code-switching, code-mixing, and language shift. This research is about code-switching. This research aims to identify the types, reasons, and errors made by Jerome Polin when he did code-switching. The theories used in this research are by Bloom and Gumperz (1972) about types of code-switching, Hoffman (1991) about reasons why people did code-switching, and surface strategy taxonomy by Dulay et al (1982) about types of error. This research was descriptive research with a qualitative approach to solving research problems. The data was taken from the Nihonggo Mantappu youtube video, and in the form of utterances. The results of this research show there are five types of code-switching used by Jerome Polin caused by various reasons. In addition, it was also found that there were errors made even though he had mastered a language.